The Man in the iron socks - Snow, Alan. (Oxford : Oxford University Press, 2008)
Arthur and his rat and pirate friends are on a mission - to save the kidnapped underlings and to thwart Snatcher's evil plans. But do they dare venture into the sinister Cheese Hall itself?And if they do, what - and who - will they find there?With nearly two hundred incredible black and white drawings, this is the second part of this astonishing illustrated journey into the unbelievably weird world of Ratbridge.
7.4
5-8.
5-8
Keywords: Magic -- Juvenile fiction; Trolls -- Juvenile fiction; Fantasy; Magic -- Fiction; Trolls -- Fiction; Magic -- Fiction; Trolls -- Fiction; Ratbridge (Imaginary place) -- Fiction; Fantastic fiction